2005
DOI: 10.1007/s11104-004-6717-4
|View full text |Cite
|
Sign up to set email alerts
|

Strategies to optimise biological nitrogen fixation in legume/grass pastures in the southern region of Chile

Abstract: Pastures in southern Chile are composed of forage grasses and associated legumes. Apart from native grass species, in many areas perennial ryegrass (Lolium perenne L.) and white clover (Trifolium repens L.) have been introduced. It is thought that most of the N in these pastures is derived from the symbiosis between rhizobium bacteria and the clover. However, various factors can limit the biological nitrogen fixation (BNF) potential. Soils of Chiloe´(southern Chile) are derived from volcanic ash (Andisols), an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
20
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 22 publications
1
20
0
Order By: Relevance
“…Chile (Campillo et al 2005), with only a single report concerning a grain legume (common bean) in Cuba (Garcia et al 2007). Addition of lime at 7.5 t ha −1 (Edmeades et al 1986) to a white clover-ryegrass pasture or 5-10 t ha −1 to a sub-clover-ryegrass pasture (Wheeler et al 1997) had no effect on DM, symbiotic dependence or N fixed by the clover (Table 10).…”
Section: Aciditymentioning
confidence: 99%
See 3 more Smart Citations
“…Chile (Campillo et al 2005), with only a single report concerning a grain legume (common bean) in Cuba (Garcia et al 2007). Addition of lime at 7.5 t ha −1 (Edmeades et al 1986) to a white clover-ryegrass pasture or 5-10 t ha −1 to a sub-clover-ryegrass pasture (Wheeler et al 1997) had no effect on DM, symbiotic dependence or N fixed by the clover (Table 10).…”
Section: Aciditymentioning
confidence: 99%
“…The surface pH of a moderately acid soil in Chile (pH 5.3-5.4) increased to 5.7-5.9 and exchangeable Al decreased from~1.0 to~0.1 cmol c kg −1 soil following surface application of lime at 4 t ha −1 (Campillo et al 2005; Table 11). The response of DM, symbiotic dependence and fixed N of white clover foliage to addition of lime and basal nutrients was measured over two growing seasons.…”
Section: Aciditymentioning
confidence: 99%
See 2 more Smart Citations
“…These soils present a high risk of acidification and usually show a high Al saturation of the ECEC (effective cation exchange capacity) where ISRID (Incentives System to Recovery Degraded Soils) has subsidised farmers to apply lime. Several studies have confirmed that addition of lime to neutralise the acidity and reduce the toxic effect of Al 3+ increases yield, forage quality, botanical composition and nitrogen symbiosis by legumes in pastures (Campillo et al 2005;Bernier and Alfaro 2006 (Sadzawka 2006). For example, a study by Bernier and Alfaro (2006) in a strongly acidic soil (pH 5.3) compared the effects of nitrate sodium and urea, where the maximum doses of N (250 kg ha -1 ) as urea clearly generated a significant acidification effect on soil (Fig.…”
Section: Soil Acidificationmentioning
confidence: 98%